DECENTERING WESTERN HRM: AN INDIGENOUS EPISTEMOLOGY APPROACH TO HUMAN RESOURCE PRACTICES - Deby Andriany; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The dominance of Western human resource management (HRM) frameworks has long shaped organizational practices globally, often promoting standardized, efficiency-driven approaches grounded in individualism and rationality. However, increasing cultural diversity and globalization have exposed the limitations of these universal models, particularly in non-Western contexts where local values, traditions, and social structures differ significantly. This study explores how indigenous epistemologies can serve as an alternative foundation for HRM, offering more contextually relevant and culturally embedded practices. Using a conceptual and interpretive qualitative approach, the research synthesizes insights from HRM literature, ethnographic studies, and indigenous knowledge systems. The findings highlight that indigenous approaches emphasize relationality, community orientation, and holistic well-being, which can enhance employee engagement and organizational effectiveness. The study also identifies key challenges, including institutional resistance and the difficulty of integrating indigenous and modern HR practices. A conceptual framework is proposed to illustrate how culturally aligned HRM practices can improve organizational outcomes. The article contributes to the discourse on decolonizing management knowledge and advancing pluralistic approaches to HRM. It concludes that integrating indigenous epistemologies is essential for developing inclusive, adaptive, and sustainable HR practices in diverse organizational contexts.